La bienveillance : un dilemme de travail pour l'enseignant novice ? De la prescription aux compromis opératoires réalisés dans sa conduite de classe - Michaël Bailleul; Sylvain Obajtek (Université de Provence, 2018)
This article questions the effects produced by the current official framework of the National Education which encourages the novice teacher to practice benevolence in his daily classroom behavior. It is based on a qualitative survey, conducted on the basis of semi-structured interviews with future professors of student civil servant schools (FES, n = 30) of the Lille Academy and a student at ESPE Lille Nord de France . The aim is to understand how they take over and redefine in their first practices and at this stage of their professional development the question of benevolence. By highlighting the representations and imagery that FES attaches to benevolence, we show at first that it can be perceived as either esoteric or under the prism of weakening the authority of the young teacher in his class conduct. In a second step, we release several profiles, differentiating themselves by the way in which the FES refer in their activity to beliefs and intentions that they problematize to themselves and for themselves.